Mundus Novus - Fonte, Ralph (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
Mundus Novus is a selection of poems from Uyayi sa mga Patay na Buwan, a longer ecopoetry collection that imagines a postapocalyptic civilization after humans have finally destroyed the planet of their birth. This collection reflects on the patterns of colonization, disregard, and destruction that has trapped humanity in cycles of violence—against each other and against nature. There is no Planet B, and climate change is our daily reality now, putting us on track to render the only world we have inhospitable. Mundus Novus attempts to answer the question: if there was indeed a Planet B, would it survive our civilization?